Experimental studies on vibrowave processes in utilization technology of combine harvester parts (case study: guide pulleys) - Anatoly P. Babichev; Vladimir N. Vesnin; Alina A Akulova; Alexander N. Mikhaylov (Advanced Engineering Research)
Introduction. The work objectives are pilot studies of vibrowave processes in the utilization technology of combine harvester parts through the example of guide pulleys, and the determination of the most effective abrasive environment. Materials and Methods . Combine harvester aggregates are considered - four idlers of the poly-V-belt with the diameter of 150 mm with various degrees of the oil consumption pollution, and old paint and soil remains. The following is accepted as an operating environment: broken abrasive disks; porcelain balls ( d =6-8mm); abrasive PT grains of 15×15; steel balls ( d =5-7mm). At the exterior check of the parts, it is noticed that all rollers have oil consumption pollution and old paint remains. The samples are contaminated approximately equally. The rollers are weighed. The treatment is performed in the vibration hydrocarbon gas unit 4×10. The processing mode is as follows: A = 2.5 mm; frequency of oscillations - 30 Hz; treatment time t = 30 min.). 2% solution of soda ash is used as a process liquid (PL). At the end of the 30-minute vibration washing and scrubbing operation, the samples were washed with water, dried and weighed. An external examination of the rollers after processing was performed. It was marked that the idler rollers were most effectively cleaned when processing in a medium consisting of the broken abrasive disks and 15×15 PT grains. However, the surface of the samples was not completely cleaned. The next stage of the experiment was performed - fault defection of the parts and determination of their conformity with the specifications. It is described how much the processed samples are suitable for the further use. Research Results . According to the measurement results, under the identical conditions for the vibratory treatment of guide pulleys, it is most effective to clean the surface using broken abrasive disks. Discussion and Conclusions . After specifying the most effective purification component, the defective parts are inspected and their TU compliance is determined. As the research results show, 3 out of 4 parts are suitable for recycling in the production.